Characterization Of Zygotic And Nucellar Embryo Of Six Indonesian Mango Cultivars Using Molecular Markers - Fatimah, Fatimah; Husni, Ali; Kosmiatin, Mia; Karsinah, Karsinah; Baroya, Mushlihatun (ANNALES BOGORIENSES, 2016)
Breeding mangoes is a long term activity and complicated. One of difficulties is polyembryonic seeds. These factors make genetic improvement through conventional parental selection and breeding slow and unpredictable. Adoption of molecular markers and genomics-based breeding strategies will likely improve predictability and breeding efficiency. The objective of this study was to evaluate the occurrence of zygotic or nucellar in polyembryony mango cultivars Garifta Merah, Lalijiwo, Manalagi, Madu, Saigon Kuning, and Saigon Merah using RAPD and SSR markers. The type of embryo (zygotic or nucellar) was evaluated by comparing the exhibiting amplification patterns, if different from the mother plant considered as zygotic and identified as nucellar if they exhibited the same banding pattern as the mother plant. Out of the 16 SSR and 16 RAPD primers evaluated, 9 primers each amplified the largest number of allele and sharply defined band. Dendogram of the SSR primers divide into three groups while RAPD primers distinguish clearly into two major groups, zygotic group and nucellar group. Based on zygotic and nucellar size, number and position, indicating no relationship between the type of embryo and embryo size, number and the position.